Peran Komunikasi Komunitas Budaya dalam Melestarikan Alat Musik Tradisional di Era Modern: Studi Etnografi pada Eksistensi Citra Musik Karinding di Balaraja - Ilham Lucky Alamsyah; Ari Suseno; Een Irianti (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
The rapid development of the times in the current era makes us forget about traditional culture, such as the traditional musical instrument Karinding, which is not widely known by people today. People are more familiar with modern musical instruments than traditional musical instruments such as guitar, bass, drums, and piano. This research aims to find out how the role and function of the Sanggar Bakar (Barak Karinding) community in maintaining its existence in today's modern era. The method used is Qualitative research method with ethnographic research type. The theory used is Functionalism Theory. The paradigm used is constructivism. Data collection techniques were conducted by in-depth interviews, observation and documentation. The results showed that Sanggar Bakar (Barak Karinding) in maintaining its existence they apply various roles and functions well and uniquely in society, so that the culture still exists in the modern era. In accordance with the theory of functionalism, all biological, instrumental, and integrative needs are met so that the spread of Karinding culture is comprehensive and sustainable.